PREVALENSI DAN MASALAH PSIKOSOSIAL PADA INFERTILITAS LAKI-LAKI: LITERATURE REVIEW - Luckyana Deviyanti; Nur Hikmatu Sa’adah; Herlina Herlina; RR. Arum Ariasih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Male infertility is a reproductive health condition affecting approximately 15% of couples worldwide, with male factors contributing to 40–50% of all cases. Beyond its biological impact, this condition imposes a substantial psychosocial burden that is often overlooked in clinical practice. This study aims to examine the prevalence of male infertility and its associated psychosocial problems, including mental health disorders, relational impacts, social stigma, and quality of life. A literature review was conducted through a comprehensive search across PubMed, Scopus, Web of Science, Google Scholar, and Indonesian national journal portals (Garuda, Sinta, Neliti). The search yielded 25 articles meeting the inclusion criteria, comprising 15 international and 10 Indonesian national publications. Global infertility prevalence reached 17.5% (lifetime) and 12.6% (period), while in Indonesia approximately 10–15% of couples of reproductive age experience infertility, with male factors accounting for about one third of cases. Among infertile men, the pooled prevalence of anxiety symptoms reached 21.37% and depression ranged from 15–40% depending on the study population. Five key psychosocial issues were identified: mental health disorders (depression, anxiety, and stress); diminished self-esteem and threats to masculine identity exacerbated by patriarchal culture; sexual dysfunction; relationship strain; and social stigma, which is particularly pronounced in the Indonesian cultural context. The study concludes that male infertility is not merely a biological problem but also a significant psychosocial stressor. A holistic, gender- and culturally-sensitive approach is recommended by integrating psychosocial support, family education, and stigma reduction into infertility services, particularly in Indonesia, where childbearing is regarded as central to the meaning of marriage.